Building security in the arctic region of eastern Siberia - Amelchugov, S.; Gofman, O.; Mitskevich, O. S.; Danilovich, E. (MATEC Web of Conferences, 2019)
The article considered the process of global warming, which is mostly represented in the northern territories of Eastern Siberia. A growth of snowfall gradient and wind load gradient, resulting in building up of snowy thermal insulation layer, which prevents ground freezing, is analyzed. According to the preliminary calculations the forecast of thawing of the permafrost will completely degrade in the second part of the 21st century. The increase of the temperature and the strength of the active layer lead to the building and structures deformation. Together with natural factors technogenic and anthropogenic factors have a great impact: effect from building operation, improper handling of pile-foundation (restricted ventilation of crawlway, no provided runoff), destruction of networks. The simulation model of climate fluctuation influence on thawing of the permafrost was developed. The melting process or correspondingly crystallization takes place during thawing/freezing of the permafrost.